Green Tea Extract Increases The Number of Granulosa Cells and E2 Serum Levels of Female Rats Exposed by Cypermethrin - Laili, Fitria Jannatul; Winarsih, Sri; Mintaroem, Karyono (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2018)
processing